Answer:

Step-by-step explanation:
The expression in the square root should be greater than or equal to zero, because square root of a negative number does not give a real number.

<span>f(x) = 1.5 x (1 - x)
f(0.8) = 1.5(0.8)(1 - 0.8) = 0.24
f(0.24) = 1.5(0.24)(1 - 0.24) ~= 0.274
f(0.274) = 1.5(0.274)(1 - 0.274) ~= 0.298
f(0.298) = 1.5(0.298)(1 - 0.298) ~= 0.314
f(0.314) = 1.5(0.314)(1 - 0.314) ~= 0.323
</span>So the answer is D : 0.24, 0.274, 0.298, 0.314, 0.323
Answhver:khglujlihluf
Step-by-step explanation:
Answer:
12 ( x+3)
Step-by-step explanation:
We can factor a 12 out of each term
12 *x + 12*3
12 ( x+3)
Start at -35
three descents of 145m adds to a total descent of 435m
-35-435=-470. the final depth is not greater than 500m